2008
DOI: 10.1097/mlg.0b013e31816c438e
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Autologous Muscle Stem Cell Survival in the Denervated Hemilarynx

Abstract: Autologous MSC therapy may be a future treatment for vocal fold paralysis. These findings support a model whereby MSCs genetically engineered to secrete CNTF and/or IGF-1 may not only promote neural regeneration, but also enhance MSC survival in an autocrine fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 20 publications
2
41
0
Order By: Relevance
“…Our histologic findings of larger myofiber diameters in GFP+ myofibers support the hypothesis that MdSCs that fuse in the partially denervated ovine tongue have the ability to attenuate muscle atrophy. Similar effects have been noted in the rodent denervated thyroarytenoid muscle . The additional finding that muscle fiber size increased beyond preinjury levels may occur secondary to the MdSCs fusing with both normally innervated and denervated myofibers, and self‐fusing to form new myofibers.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our histologic findings of larger myofiber diameters in GFP+ myofibers support the hypothesis that MdSCs that fuse in the partially denervated ovine tongue have the ability to attenuate muscle atrophy. Similar effects have been noted in the rodent denervated thyroarytenoid muscle . The additional finding that muscle fiber size increased beyond preinjury levels may occur secondary to the MdSCs fusing with both normally innervated and denervated myofibers, and self‐fusing to form new myofibers.…”
Section: Discussionsupporting
confidence: 59%
“…The utilization of autologous muscle derived stem cell (MdSC) therapy to treat the damaged tongue is appealing. MdSCs have the potential to restore both muscular deficits and dynamic function . The tongue is technically easy to inject and is highly accessible.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that tissue-engineered muscle thickness (survival) is directly dependent on innervation, and that atrophy will occur without innervation, just as atrophy occurs when innate myofibers become acutely denervated. 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…Cell therapy is an attractive strategy for tissue regeneration, but one of the important aspects of cell therapy is keeping the cells at the site, maintaining the survival, and maximizing their function. Halum et al 40 reported that insulin-like growth factor-1 and ciliary neurotrophic factor promoted autologous MSCs survival in the treatment of vocal folds paralysis. Scaffolds, including HA-based hydrogels 41,42 and atelocollagen, 12 were used as delivery carrier of cells transplantation for vocal fold scarring.…”
Section: Discussionmentioning
confidence: 99%